Analysis of the selection of cross-sectional areas of power transmission lines - Abdurakhim D. Taslimov; Farrux M. Raximov; Feruz, M. Rakhimov (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
Relevance: In the development of the electric power industry of our republic, as well as in the reliable supply of the necessary amount of electric energy to agriculture and industry, the issue of selecting the main parameters of electrical networks, utilizing modern approaches, and implementing comprehensive measures—including optimizing, upgrading, and improving the reliability of power transmission networks—remains highly relevant. In particular, the problem of choosing the most optimal cross-sectional area of conductors for power transmission lines is of great importance. Furthermore, determining the optimal parameters of electrical networks, conducting theoretical and scientific research to enhance their reliability, and obtaining relevant recommendations for the design, construction, modernization, and operation of rural electrical networks are also critical issues. Successfully addressing this problem and improving the reliability of electricity supply to consumers, as well as enhancing the quality of transmitted electric energy, can be achieved by selecting the cross-sectional area of power transmission line conductors based on the economic interval method. Aim: analysis and justification of the use of economic interval methods for selecting the cross-sectional area of rural power networks with dynamically varying loads. Methods: the method of economic intervals and the comparative analysis methods of technical and economic indicators are used. Results: when selecting the cross-sectional area of dynamically variable load rural power networks, it is necessary to determine the boundaries of economic load intervals without considering the time-based variation of the load. By using shift coefficients of the economic interval boundaries, it becomes possible to determine the boundaries of economic intervals for any law of load growth. Subsequently, a decision is made on selecting the optimal cross-sectional area.